If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4c + 11 + -7n = -13 Reorder the terms: 11 + 4c + -7n = -13 Solving 11 + 4c + -7n = -13 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + 4c + -11 + -7n = -13 + -11 Reorder the terms: 11 + -11 + 4c + -7n = -13 + -11 Combine like terms: 11 + -11 = 0 0 + 4c + -7n = -13 + -11 4c + -7n = -13 + -11 Combine like terms: -13 + -11 = -24 4c + -7n = -24 Add '7n' to each side of the equation. 4c + -7n + 7n = -24 + 7n Combine like terms: -7n + 7n = 0 4c + 0 = -24 + 7n 4c = -24 + 7n Divide each side by '4'. c = -6 + 1.75n Simplifying c = -6 + 1.75n
| 1+3x+3=-11 | | h=-4+7t-5t^2 | | 8a=0.48 | | 4xy+6yz-5xz-4xy= | | 33.33x+y=4 | | 5y+12-8y=-42 | | x+(x*.13)=49.15 | | 9-9x=-171 | | 8x=10x-6 | | 8x+7x-4=4x+5x-9 | | 13x-3=x+53 | | 11+7q=12+6q | | 7b+7=6b | | -3+5x-3x=-15 | | -7-2j=5j | | 3k-5-7k=-37 | | 2lnx=21 | | 4x-1=-3x+13 | | 3x+42-5x=2-9x+5 | | X+5x=450 | | X+4+2x=20 | | 3lnx=22 | | 3(5x-2)+3(9-2x)-2(4x+1)=-1 | | 0.505=0.505x | | a(p+q)+2b(p+q)+a(p-q)+2b(p-q)= | | -3(3p+3)-2(4-8p)-3(9+2p)=0 | | -6.8+2.6+x=9.2 | | 2x^2-53x+141=0 | | 5(x+4)-16=2(x+3)-2 | | -8(3b+2)+(25b-5)=0 | | 20y^2+4y-7=0 | | 22+5=-3x+15 |